Self-esteem and organizational values in university students from Lima - Loli Pineda, Alejandro (2000)
The selfesteem and the organizational values in students of the public and private university of Lima, it is a study developed in a sample of 1464 subject of a Public University and a Private University of the oldest and traditional of the country, in order to knowing the hierarchy of values organizecionales perceived by the university youths that expect from the organization in which you they would want to work to the culmination of their studies; the relationship between the selfesteem and certain demographic features, and also the differences among the values organizational and this demographic features. The results indicate that the university students give bigger importance to the cleaning, service to the client, and to the quality of the product and of the service, and smaller importance to the honesty, to the responsibility and the respect to the person. Equally, he/she is positive correlation between the personal selfesteelm and the value cleaning, negative between the selfesteem and the value responsibility and respect to the person. The crossed analysis of the levels of self-esteem for universities indicates us that difference significant statistic doesn't exist among the Public University and Deprived nevertheless there is prevalence of the low selfesteem as much as in the first one as in second o' clock, except for when the gender intervenes where the difference is significant with prevalence of the low selfesteem in mens and mediates in women.